Improving the Ability of Indonesian Language Teachers in Developing Differentiated Teaching Materials for Writing Procedural Text Skills Based on Local Wisdom - Haryadi, Ardi Mulyana; Julianto, Agus Tedi; Mulyasari, Iis; Hendarsyah, Hendarsyah; Kurnia, Aji; Kusumah, Riyana; Cukanda, Cucu; Novianti, Vivi; Andriani, Dian; Mulyani, Nenti Antalanti; Nurbaiti, Nurbaiti; Setiabudi, Dedi; Herlina, Lina; Rohmani, Tina Yunia; Fahroji, Fahroji; Mardiana, Mira (Indonesian Journal of Community Empowerment (IJCE), 2024)
This community service program aimed at enhancing the ability of Indonesian Language teachers in Garut and Sumedang to develop differentiated instructional materials for teaching procedural writing skills based on local wisdom. Through a collaborative mentoring approach, teachers were equipped to integrate local wisdom into procedural text teaching, making the material more relevant and contextual to students' lives. The program demonstrated significant improvement in teachers' understanding and practical skills in designing instructional materials that reflect local culture. The evaluation results showed a notable increase in teachers' ability to create and implement differentiated materials in the classroom. This initiative is expected to have a long-term positive impact on the quality of teaching and procedural writing skills in these regions.